Fractal aggregates evolution during flocculation - Moruzzi, R. B. [UNESP]; de Oliveira, A. L. [UNESP]; de Almeida, T. [UNESP] (FapUNIFESP (SciELO), 2018)
- A temporal analysis of fractal aggregates during water flocculation is presented. Water was prepared using kaolin solution and a non-intrusive image-based analysis method was used for two-dimensional fractal dimension assessment (dF). The dF values were determined for aggregates larger than 270 µm from 100 images taken in each combination of velocity gradients (Gf) and flocculation times (Tf). The Gf values of 20, 30, 40, 50 and 60 s-1 and Tf values of 2 to 180 minutes were studied, with a ΔTf of 1 minute for 2 ≤ Tf ≤ 10 minutes and a ΔTf of 5 minutes for 10 ≤ Tf ≤ 180 minutes. Results showed that dF tends toward stability from a Tf of 40 minutes, with distinct levels in each Gf. Further, dF values decrease from 1.80 to 1.35 for Gf from 20 to 60 s-1.
Keywords: Flocculation; Fractal aggregates; Temporal evolution